2017
DOI: 10.1155/2017/1734151
|View full text |Cite
|
Sign up to set email alerts
|

New Targets forZikaVirus Determined by Human-Viral Interactomic: A Bioinformatics Approach

Abstract: Identifying ZIKV factors interfering with human host pathways represents a major challenge in understanding ZIKV tropism and pathogenesis. The integration of proteomic, gene expression and Protein-Protein Interactions (PPIs) established between ZIKV and human host proteins predicted by the OralInt algorithm identified 1898 interactions with medium or high score (≥0.7). Targets implicated in vesicular traffic and docking were identified. New receptors involved in endocytosis pathways as ZIKV entry targets, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 95 publications
2
11
0
Order By: Relevance
“…Viral structural glycoproteins, in particular envelope E glycoprotein, mediate binding to cellular receptors, thereby triggering endocytotic pathways. These interactions between cellular receptors and glycoproteins allow ZIKV to infect specific cellular types including fibroblasts, immature dendritic cells, epidermal keratinocytes, and stem-cell-derived human neural progenitor cells [ 7 ]. The uptake of viral particles occurs primarily through clathrin-dependent endocytosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Viral structural glycoproteins, in particular envelope E glycoprotein, mediate binding to cellular receptors, thereby triggering endocytotic pathways. These interactions between cellular receptors and glycoproteins allow ZIKV to infect specific cellular types including fibroblasts, immature dendritic cells, epidermal keratinocytes, and stem-cell-derived human neural progenitor cells [ 7 ]. The uptake of viral particles occurs primarily through clathrin-dependent endocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…This completes the entry process, which implies the delivery of viral RNA into the cytoplasm of the host cell. The positive-sense RNA is translated into a polyprotein, which is subsequently cleaved to release structural and NS proteins [ 7 ]. Cellular compartments such as the endoplasmic reticulum (ER) and the Golgi apparatus, seem to be crucial for viral replication and propagation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that its invasion relies on a more complex interaction of AXL receptor, since its experimental ablation does not prevent the viral invasion ( Wells et al, 2016 ). Indeed, ZIKV would be able to infect different types of neuronal cells through the exploitation of multiple cell surface receptors and cytosolic components ( Esteves et al, 2017 ). This impairs multiple cellular processes, causing cell death, inflammatory response, disrupting the normal biological development ( Rosa-Fernandes et al, 2019 ).…”
Section: The Aftermath Of Zikv Infection: Prenatal Neuronal Impairmenmentioning
confidence: 99%
“…IFN signaling depends on the interactions with entry cell receptors, such as AXL (a cell surface TAM-family receptor) ( Lemke, 2013 ; Meertens et al, 2017 ). AXL is pivotal for flaviviruses and is expressed in several cells, such as some placental cells, astrocytes, microglia, oligodendrocytes, human radial glia and NPCs ( Li et al, 2016 ; Akkermann et al, 2017 ; Esteves et al, 2017 ; Meertens et al, 2017 ). Its precise role remains uncertain; it could act as an entry factor for ZIKV endocytosis ( Meertens et al, 2017 ; Ojha et al, 2019 ) or antagonize type I IFN signaling ( Chen et al, 2018 ).…”
Section: The Aftermath Of Zikv Infection: Prenatal Neuronal Impairmenmentioning
confidence: 99%